A novel mode for transcription inhibition mediated by PNA-induced R-loops with a model in vitro system - D’Souza, Alicia D. (Biochim Biophys Acta, 2018)
The selective inhibition of transcription of a chosen gene by an artificial agent has numerous applications. Usually, these agents are designed to bind a specific nucleotide sequence in the promoter or within the transcribed region of the chosen gene. However, since optimal binding sites might not exist within the gene, it is of interest to explore the possibility of transcription inhibition when the agent is designed to bind at other locations. One of these possibilities arises when an additional transcription initiation site (e.g. secondary promoter) is present upstream from the primary promoter of the target gene. In this case, transcription inhibition might be achieved by inducing the formation of an RNA-DNA hybrid (R-loop) upon transcription from the secondary promoter. The R-loop could extend into the region of the primary promoter, to interfere with promoter recognition by RNA polymerase and thereby inhibit transcription. As a sequence-specific R-loop-inducing agent, a peptide nucleic acid (PNA) could be designed to facilitate R-loop formation by sequestering the non-template DNA strand. To investigate this mode for transcription inhibition, we have employed a model system in which a PNA binding site is localized between the T3 and T7 phage RNA polymerase promoters, which respectively assume the roles of primary and secondary promoters. In accord with our model, we have demonstrated that with PNA-bound DNA substrates, transcription from the T7 promoter reduces transcription from the T3 promoter by 30-fold, while in the absence of PNA binding there is no significant effect of T7 transcription upon T3 transcription.